'We needed to talk about it': The experience of sharing the emotional impact of health care work as a panellist in Schwartz Center Rounds® in the UK. Issue 1 (January 2021) - McCarthy, Imelda; Taylor, Cath; Leamy, Mary; Reynolds, Ellie; Maben, Jill
Objectives: Schwartz Center Rounds® ('Rounds') are multidisciplinary forums where health care staff come together to reflect upon the emotional impact of their work. In each Round, a small number of staff (panellists) share experiences through stories to trigger reflection in audience members. Previous research has identified impacts associated with Rounds' attendance, but little is known about the experience and impact of Rounds from panellists' perspectives. This study is the first to explore the role of disclosure and reflection through storytelling in Rounds, specifically exploring panellists' motivations, experiences and reported impacts associated with panel participation. Methods: Interviews with 50 panellists, from nine case-study sites in the United Kingdom, representing acute, community and mental health National Health Service trusts and hospices. Data were analysed using thematic analysis. Results: Most panellists spoke positively about their experience of sharing their stories in Rounds. Reported impacts included: increased emotional resilience and acceptance of experiences; reduced negative assumptions about colleagues and increased approachability and trust increasing tolerance and compassion; the creation of a space to stop and think and to reframe negative patient experiences facilitating greater empathy and emotional disclosure becoming more visible and normative, thereby helping change culture. Impacts on staff were similar regardless of contextual variability, including their professional group or role, with the exception of impact on patient care, which was not mentioned by non-clinical staff. The extent of panel preparation and audience characteristics (e.g. size, composition and response to their stories) influenced panellists' experiences and outcomes. Conclusions: Rounds highlight the important role of disclosure and reflection through storytelling to support panellists with the emotional aspects of their work, providing a space for support with the emotional demands of health care, reducing the need for employees to be stoic. Panel participation also offers an important source of validation in organizations marked by scrutiny.